Molecular evolution and expression profile of the chemerine encoding gene RARRES2 in baboon and chimpanzee - González Álvarez, Rafael; Garza Rodríguez, María de Lourdes; Delgado Enciso, Iván; Treviño Alvarado, Víctor Manuel; Canales del Castillo, Ricardo; Martínez de Villarreal, Laura Elia; Lugo Trampe, Ángel; Tejero, María Elizabeth; Schlabritz Loutsevitch, Natalia E.; Rocha Pizaña, María del Refugio; Cole, Shelley A.; Reséndez Pérez, Diana; et al. (2015)
Background: Chemerin, encoded by the retinoic acid receptor responder 2 (RARRES2) gene is an adipocytesecreted protein with autocrine/paracrine functions in adipose tissue, metabolism and inflammation with a recently described function in vascular tone regulation, liver, steatosis, etc. This molecule is believed to represent a critical endocrine signal linking obesity to diabetes. There are no data available regarding evolution of RARRES2 in non-human primates and great apes. Expression profile and orthology in RARRES2 genes are unknown aspects in the biology of this multigene family in primates. Thus; we attempt to describe expression profile and phylogenetic relationship as complementary knowledge in the function of this gene in primates. To do that, we performed A RT-PCR from different tissues obtained during necropsies. Also we tested the hypotheses of positive evolution, purifying selection, and neutrality. And finally a phylogenetic analysis was made between primates RARRES2 protein. Results: RARRES2 transcripts were present in liver, lung, adipose tissue, ovary, pancreas, heart, hypothalamus and pituitary tissues. Expression in kidney and leukocytes were not detectable in either species. It was determined that the studied genes are orthologous. Conclusions: RARRES2 evolution fits the hypothesis of purifying selection. Expression profiles of the RARRES2 gene are similar in baboons and chimpanzees and are also phylogenetically related.